Bahauddin nakshband’s role in improving human’s spirituality - NEGMATOVNA, NAVRUZOVA GULCHEHRA (The journal of contemporary issues in business and government, 2021)
The article presents a philosophical analysis of the spiritual heritage of the seventh feast of the holy Bukhara, the great Bahauddin Nakshband(1318-1389), known as Shoh Nakshband, Xojai Buzurg, Balogardon, a feast of the 16th ring of the Sufi tariqah of Khojagan Nakshbandiya based on sources and highlights their important aspects for the education of a perfect person. The novelty of the article lies in the fact that work of Bahauddin Nakshband “Avrod” is translated based on handwritten and translated sources. In the article Bahauddin Nakshband’s words of wisdom for improving human’s spirituality which are written in Muhammad Porso’s book “ Risolai Qudsiya” and Abul Muhsin Muhammad Boqir’s book called “Maqomoti Hazrati Khoja Nakshband” are analysed. In this article advantages of Nakshbandiya way of perfection founded by Bahauddin Nakshband is written. In the article the personality of the founder of a way of perfection Nakshbandiya Bakhauddin Nakshband reveals as conscientiousness and honesty symbol, exploration of life and creativeness in period of independence of Republic of Uzbekistan, his spiritual heritage. Besides this, the understanding of his correct way of life and his understanding of honesty and conscientiousness his edification of honesty and decency, meaning of motto “In heart-god, and hands-in work” and application of these ideas in modern Uzbekistan is given.